FAKTOR YANG MEMPENGARUHI MASYARAKAT TIONGHOA MEMILIH AGAMA BUDDHA: STUDI KASUS DI DESA KEDAUNG BARAT KECAMATAN SEPATAN TIMUR KABUPATEN TANGERANG - Marjoko, Sabar (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2023)
This study aims to determine the factors that influence the Chinese community in the village of West Kedaung to choose Buddhism as a belief. The method in this research is qualitative with a case study approach. Data collection techniques and instruments using observation, interviews and documentation. The validity of the research instrument was tested by conducting persistent observation and triangulation between sources. Data analysis techniques use the Miles & Huberman model. The subject of this research is the Chinese community in West Kedaung Village. The conclusions of this study are (1) Biogenetic motives are the most dominant motive for the Chinese community in Kedaung Barat Village choosing Buddhism. (2) The role of parents in instilling an understanding of Buddhist teachings is an important key in shaping children's beliefs. (3) Parents play a role so that children get a good quality education academically and at the same time obtain moral guidance through education that is characterized by religion, especially schools of Buddhist foundations. (4) Good upbringing, strengthening cultural and religious values ​​is the key for the Chinese community in Kedaung Barat Village so that children continue to choose Buddhism and prevent religious conversions. (5) Parents play a role in providing an understanding that religious differences are not something that needs to be contested, but parents are obliged to take care that children inherit the traditions and religion of their parents as a form of devotion.